A Lyapunov Based Model Reference Adaptive Control of A Quadrotor - Akgun, Onur; Subasi, Evren; Turker, Turker (IEEE, 2017)
Model reference adaptive controller is proposed to control the position of a quadrotor with uncertain model parameters. The controller design procedure is provided considering position and attitude dynamics as outer and inner loops respectively. Reference signals for roll and pitch angles are obtained from the outer loop controller while the inner loop controller drives the tracking error of roll and pitch angle dynamics to zero. Stability analysis for both inner and outer loop error dynamics are performed and the adaptation laws are derived based on Lyapunov stability theory. Since the reference models can also be assigned separately for inner and outer loops, the speed of the responses of position and attitude dynamics are adjusted independently improving the control performance. The viability and the success of the proposed controller are tested through simulations studies performed for different tracking scenarios.
Keywords: DESIGN; Engineering